Chronotherapy with low-dose modified-release prednisone for the management of rheumatoid arthritis: a review - Beltrametti SP; Ianniello A; Ricci C (Dove Medical Press, 2016)
Stefano Paolo Beltrametti,1 Aurora Ianniello,2 Clara Ricci3 1Department of Rheumatology, S. Andrea Hospital, Vercelli, 2Rheumatology Outpatient Clinic, Novara, 3Primula Multimedia S.p.A, Pisa, Italy Abstract: To date, rheumatoid arthritis (RA) remains a debilitating, life-threatening disease. One major concern is morning symptoms (MS), as they considerably impair the patients’ quality of life and ability to work. MS change in a circadian fashion, resembling the fluctuations of inflammatory cytokines such as interleukin-6, whose levels are higher in RA patients compared to healthy donors. Conversely, serum levels of the potent anti-inflammatory glucocorticoid cortisol are similar to that of healthy subjects, suggesting an imbalance that sustains a pro-inflammatory state. From a therapeutic point of view, administering synthetic glucocorticoids (GCs) to RA patients represents an optimal strategy to provide for the inadequate levels of cortisol. Indeed, due to their high efficacy in RA, GCs remain a cornerstone more than 60 years after their first introduction, and despite the development of a wide range of targeted agents. However, to improve safety, low-dose GCs have been introduced, that have demonstrated high efficacy in reducing disease activity, radiological progression, and improving patients’ signs and symptoms especially in early RA when added to conventional disease-modifying antirheumatic drugs. A further improvement has been provided by the development of modified-release prednisone, which, by taking advantage of the circadian fluctuations of inflammatory cytokines, cortisol and MS, is given at bedtime to be released approximately 4 hours later. Several studies have already demonstrated the efficacy of this agent on disease activity, MS, and quality of life in the setting of established RA. Moreover, preliminary studies have shown that this new formulation not only has no impact on the adrenal function, but likely improves it. This review is a comprehensive, updated summary of the current evidence on the use of GCs in RA, with focus on the efficacy and safety of low-dose prednisone and modified-release prednisone, the latter representing a rational, cost-effective, and tailored approach to maximize the benefit/risk ratio in RA patients. Keywords: glucocorticoids, rheumatoid arthritis, modified-release prednisone, safety, efficacy, adrenal function